TRANSFORMATION OF THE EDUCATION SYSTEM IN THE CONDITIONS OF DIGITALIZATION OF THE ECONOMY AND SOCIETY - KOSTETSKYI, Pavlo; KUTSENKO, Vladyslav (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The article is devoted to the study of the peculiarities of the transformation of the education system in accordance with the requirements of the digital economy and society. In the digital economy, information and knowledge are becoming one of the most important strategic resources. Skills in working with software technologies and digital products are becoming in demand not only for highly specialized IT professionals, but also for workers in all sectors and industries. The article analyzes the current level of demand for specialists in the field of information and communication technologies, as well as the structure of digital skills of the population in European countries. The study of the key trends of digitalization of society proved that working with information is becoming one of the most important skills in the modern world, and digital technologies and products are used in almost all sectors of the economy. The analysis of modern directions of digitalization of educational institutions proved that the most important of them are the digitalization of the educational process, the digitalization of science, the digitalization of management and marketing, and the digitalization of infrastructure. It was determined that the digitalization of educational institutions provides an increase in their competitiveness, cost savings, ensuring the appropriateness of the user experience, as well as increasing their flexibility and adaptability. At the same time, the digitalization of education provides a number of advantages for students, in particular, in terms of the ability to work with information, an individual learning trajectory, and the expansion of choice. However, the digitalization of education is also associated with a number of disadvantages, in particular, regarding the increase in psychological tension for the recipients of educational services and significant efforts and costs related to the organization of digital education. It is substantiated that the main directions of the digital transformation of educational institutions should be the creation of a digital infrastructure, the formation of a sufficient level of digital skills of teachers, the improvement of the digital capacity of educational institutions, the introduction of a digital component in educational programs, the use of digital education resources, the development of a digital educational environment, and the introduction of digital assessment systems.